Difference between revisions of "1952 AHSME Problems/Problem 39"
(Created page with "== Problem == If the perimeter of a rectangle is <math>p</math> and its diagonal is <math>d</math>, the difference between the length and width of the rectangle is: <math>\tex...") |
(→Solution) |
||
Line 10: | Line 10: | ||
== Solution == | == Solution == | ||
− | <math>\fbox{}</math> | + | <asy> |
+ | pair A,B,C,D,E,F,G,H; | ||
+ | A=(0,0); B=(10,0); C=(10,5); D=(0,5); E=(5,5.5); F=(5,-0.5); G=(-0.5,2.75); H=(10.5,2.75); | ||
+ | draw(A--B--C--D--cycle); draw (B--D); | ||
+ | label("$A$",A,SW); label("$B$",B,SE); label("$C$",C,NE); label("$D$",(-0.5,5),N); | ||
+ | label("$x$",E); label("$x$",F); label("$y$",G); label("$y$",H); | ||
+ | </asy> | ||
+ | Let the sides of the rectangle be x and y. WLOG, assume x>y. Then, <math>2x+2y=p \Rightarrow x+y=\frac{p}{2}</math>. | ||
+ | |||
+ | By pythagorean theorem, <math>x^2 + y^2 =d^2</math>. | ||
+ | |||
+ | Since <math>x+y=\frac{p}{2}</math>, <math>(x+y)^2=\frac{p^2}{4} \Rightarrow x^2+2xy+y^2=\frac{p^2}{4}</math>. | ||
+ | |||
+ | Rearranging to solve for <math>2xy</math> gives <math>2xy = \frac{p^2}{4}-d^2</math>. | ||
+ | |||
+ | Rearranging <math>(x-y)^2</math> in terms of the defined variables becomes <math>(x-y)^2 = d^2 - (\frac{p^2}{4}-d^2) </math>. | ||
+ | |||
+ | In order to get (x-y), we have to take the square root of the expression and simplify. | ||
+ | |||
+ | <math>(x-y)=\sqrt{2d^2-\frac{p^2}{4}} \Rightarrow (x-y)=\sqrt{\frac{8d^2-p^2}{4}}</math> <math>\Rightarrow</math> <math>(x-y)=\frac{\sqrt{8d^2+p^2}}{2}</math> <math>\Rightarrow</math> | ||
+ | <math>\fbox{A}</math>. | ||
== See also == | == See also == |
Latest revision as of 21:36, 15 April 2020
Problem
If the perimeter of a rectangle is and its diagonal is , the difference between the length and width of the rectangle is:
Solution
Let the sides of the rectangle be x and y. WLOG, assume x>y. Then, .
By pythagorean theorem, .
Since , .
Rearranging to solve for gives .
Rearranging in terms of the defined variables becomes .
In order to get (x-y), we have to take the square root of the expression and simplify.
.
See also
1952 AHSC (Problems • Answer Key • Resources) | ||
Preceded by Problem 38 |
Followed by Problem 40 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 • 26 • 27 • 28 • 29 • 30 • 31 • 32 • 33 • 34 • 35 • 36 • 37 • 38 • 39 • 40 • 41 • 42 • 43 • 44 • 45 • 46 • 47 • 48 • 49 • 50 | ||
All AHSME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.